Internetês na EJA via whatsapp: um desafio a escrita formal? - Costa, Neusilena de Brito (2020)
Internetese was a term created to conceptualize the language used in various chats and chats on the internet since its emergence in the 20th century and encompasses all use of written language in virtual media. In line with this inevitable use of online language concomitant to the use of the standard language, the present study, on the dialogue between the internet and Portuguese, investigated the use of the Whatsapp application and its approach to formal writing, in Youth and Adult Education rooms, of a municipal public school in João Pessoa. When dealing with the fragmentation of texts from digital culture and the speed required in their production, we realized that the text composition with regard to students' textual productions may undergo a standardization similar to that of grammatical norms, which gives this production a responsive attitude anchored in students' linguistic competence. The objective of this dissertation was to investigate singularities in the use of internetese, in the Education of Youths and Adults in writing and in the rewriting of texts in analog and digital supports. To follow this discursive path, we are guided by the studies of genres in Bakthin (1981, 2003). With regard to digital textual production, multimodality and multi-tools, we support Rojo and Moura (2012) and Bisognin (2009), in order to highlight the relevance of using the internet in the digital environment, in addition to apprehending characteristics related to linguistic competence according to Hymes (1995), who defends the subject's ability to circulate in the target language, in an appropriate way and combined with the influence of this application in education. In this way, we confirm the need to improve the rules of the formal language concomitant to the use of internetese as a variant in a different means of interaction. In order to know characteristics about the researched subjects, we use the ethnographic process about which Fino (2003) affirms that this constitutes a participant observation, that is, an investigation that is characterized by a period of intense social interactions between the researcher and the subjects. In the case of our research, this process aimed to investigate the use of the Internet and Portuguese language variants, in addition to advancing the quality of textual productions of the target audience, considering that what drives writing in everyday life are real situations. As a result of this research, we confirm progress with regard to the conscious use of internetese as a variant of the mother tongue.